Pengaruh Persepsi Kemudahan, Persepsi Keamanan, Persepsi Manfaat, dan Financial Literacy terhadap Minat Penggunaan E-wallet pada Generasi Z di Kabupaten Boyolali - Putri Tarisa; Dika Puspitaningrum (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The rapid advancement of digital technology has transformed the global financial landscape, including in Indonesia, with the increasing use of e-wallets as modern payment methods. Generation Z, raised in the digital age, represents the primary users; however, their understanding of financial management and digital security varies. This study explores the impact of perceived ease of use, perceived security, perceived usefulness, and financial literacy on the intention to adopt e-wallets among Generation Z in Boyolali Regency, Indonesia. A quantitative explanatory approach was used, with data collected through an online questionnaire from 108 participants selected through purposive sampling based on age, residence, and e-wallet experience. The instrument employed a five-point Likert scale, which was validated and found reliable (Cronbach’s Alpha > 0.87). Data analysis was performed using multiple linear regression via SPSS version 25. The results revealed that all independent variables significantly influenced the intention to adopt e-wallets (F = 115.463; Sig. = 0.000). Specifically, perceived security, perceived usefulness, and financial literacy showed positive and significant effects, while perceived ease of use did not. The model's R² of 0.818 indicates that it explains 81.8% of the variance in e-wallet adoption intention. These findings highlight the critical role of security and financial literacy in shaping trust and behavior toward digital financial services. The study extends the Technology Acceptance Model (TAM) by adding financial literacy as a determinant, providing practical insights for service providers and policymakers to enhance digital financial literacy and security for sustainable digital inclusion among Generation Z in semi-urban areas.